MODEL-Based Performance Quality Assessment for IoT Applications - Kh., Teeba Ismail; Hamarash, Ibrahim I. (International Journal of Interactive Mobile Technologies (iJIM), 2021)
The number of applications incorporating Internet of Things (IoT) concepts increases extraordinarily. This increase cannot continue without high-quality assurance. There are some difficulties in testing IoT applications; the system heterogeneity, test cost and time are taken to test the system, and the precision percentage of test results. A well-known and possibly the best solution to overcoming these difficulties is to model the system for evaluation purposes, known as model-based testing (MBT). This paper aims to design a model-based testing approach to assess IoT applications performance quality attributes. The ISO 25000 quality model is used as a standard for software quality assurance applications. IoTMaaS is used as a case study to implement the methodological approach. The possible test cases were generated using the ACTS combinatorial test generation tool. The performance metrics of each test case were monitored until the optimum test case was identified, with the shortest response time and the least amount of resources used. The proposed testing method appears to be successful, according to the results.